2011
DOI: 10.1530/eje-10-1195
|View full text |Cite
|
Sign up to set email alerts
|

FABP 4 is associated with inflammatory markers and metabolic syndrome in morbidly obese women

Abstract: ObjectiveThe adipocyte/macrophage fatty acid-binding protein 4 (FABP4) has been described as a biomarker for adiposity and metabolic syndrome (MS). The aims of this study were to assess the relationship between FABP4 and inflammatory cytokines related to obesity, and to evaluate FABP4 mRNA expression in visceral and subcutaneous adipose tissue in non-diabetic morbidly obese women versus healthy lean women.MethodsWe analyzed circulating levels of FABP4 in 81 Spanish women: 38 lean (body mass index (BMI)<25 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
69
4
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 117 publications
(84 citation statements)
references
References 34 publications
9
69
4
2
Order By: Relevance
“…Until recently, the biological functions of aP2 in the pathogenesis of chronic diseases have been attributed exclusively to its intracellular action. However, newer studies have demonstrated that aP2 is released from adipocytes; its levels are signifi cantly increased in experimental and human obesity and strongly correlate with cardiometabolic diseases in numerous human studies (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). We have also shown that the secreted form of aP2 is a bona fi de adipokine that regulates systemic metabolism, and that antibody-mediated neutralization exhibits potent antidiabetic activity in preclinical models ( 15 ).…”
Section: A Nonclassical Vesicular Pathway Mediates Ap2 Secretion Uponmentioning
confidence: 80%
See 1 more Smart Citation
“…Until recently, the biological functions of aP2 in the pathogenesis of chronic diseases have been attributed exclusively to its intracellular action. However, newer studies have demonstrated that aP2 is released from adipocytes; its levels are signifi cantly increased in experimental and human obesity and strongly correlate with cardiometabolic diseases in numerous human studies (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). We have also shown that the secreted form of aP2 is a bona fi de adipokine that regulates systemic metabolism, and that antibody-mediated neutralization exhibits potent antidiabetic activity in preclinical models ( 15 ).…”
Section: A Nonclassical Vesicular Pathway Mediates Ap2 Secretion Uponmentioning
confidence: 80%
“…These studies also demonstrated that circulating aP2 levels are signifi cantly increased in dietary and genetic models of obesity, and that neutralizing circulating aP2 with a polyclonal antibody improved metabolic parameters and diabetes in mice ( 15 ). A growing body of association studies in humans also shows that circulating aP2 levels are positively correlated with obesity, metabolic pathologies, and cardiovascular disease (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). In addition, recent studies have revealed multiple other potential roles for extracellular aP2 ( 27,28 ).…”
Section: Cell Culturementioning
confidence: 95%
“…Cash et al (39) first suggested that DNA hypomethylation is involved in the development of cardiovascular disease, and evidence from animal studies has suggested that global DNA hypomethylation is associated with atherosclerotic lesions. A number of previous reports have focused on alterations in the DNA methylation of specific genes associated with AS (40,41). Global hypomethylation affects CpG dinucleotides in repetitive elements and in certain gene-specific promoter CpG islands (42).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing serum aFABP levels are closely associated with impaired glucose metabolism and may also be considered a useful indicator of the development of type 2 diabetes 13 . Increasing aFABP levels have been shown to be associated with inflammatory markers such as CRP and interleukin-6 in obese individuals and those with metabolic syndrome 14 . The association of AFABP and CRP with metabolic syndrome is often explained by the association with obesity.…”
Section: Discussionmentioning
confidence: 99%